The motive for the action of online gambling as an additional livelihood during social restrictions due to the Covid-19 pandemic - Yayi Putri Dwihayuni; Agus Machfud Fauzi (Jurnal Sosiologi Dialektika, 2021)
Gambling is one of the sub-cultural deviations that have mushroomed in society. Gambling has so far been prohibited by law, but during the difficult times of the pandemic and the implementation of social restrictions in Nganjuk Regency, gambling has become a classic excuse in the midst of the current difficult economy. However, during the social restrictions gambling was mostly done online (via electronic media). This study aims to research and find the background of why many people like to play online gambling. The research method was qualitative. Primary data were obtained through observation and in-depth interviews. This study finds factors that influence the prevalence of gambling during social restrictions, both internal and external factors. This study also finds that online gambling has many types such as lottery gambling, dice, games using cash as the dowry for bets. On the other hand, online gambling is done as entertainment or a hobby. This study concludes that the Covid-19 pandemic causes social problems so that online gambling is used as an additional livelihood and as a hobby by the people in Nganjuk Regency.